Perancangan Animasi Undangan Digital Dengan Menggunakan Adobe Flash Proffessional CS6 - Doni Permana Putra (Universitas Labuhanbatu, 2021)
Advances in information and communication technology have been used as alternative solutions to overcome several problems. One of the uses of information for online wedding invitations. With online wedding invitations, information delivery is faster and more efficient, and the content can be more varied. The purpose of this project is to create interesting and informative content that is packaged in the form of motion graphic video using the Adobe flash professional application.